The world says no to war : demonstrations against the war on Iraq - Walgrave, Stefaan, 1966-; Rucht, Dieter (Social movements, protest, and contention ;, 2010)
On February 15, 2003, the largest one-day protest in human history took place as millions of people in hundreds of cities marched in the streets, rallying against the imminent invasion of Iraq. This was activism on an unprecedented scale. The World Says No to War strives to understand who spoke out, why they did, and how so many people were mobilized for a global demonstration. Using surveys collected by researchers from eight countries--Belgium, Britain, Germany, Italy, the Netherlands, Spain, Switzerland, and the United States.